Multi-constrained path computation for inter-domain QoS-capable services. (1st January 2014) - Djarallah, Nabil Bachir; Pouyllau, Hélia; Lahoud, Samer; Cousin, Bernard
Computing inter-domain multiprotocol label switching traffic engineering label switched path (MPLS-TE LSP) through a pre-determined sequence of domains is quite straight as each path computation element (PCE), using the backward recursive PCE-based computation (BRPC), knows who is the next to be contacted in order to continue the computation. The optimality of the inter-domain MPLS-TE LSP path depends strongly on the choice of the pre-determined sequence of domains on which the calculation works. In this paper, we propose a novel procedure allowing a forward discovery of multiple inter-domain sequences and the computation of constrained inter-domain paths for MPLS-TE LSPs over these domains sequences. Other issues around the inter-domain path computation, such as route discovery and inter-domain loop avoidance, are investigated. Experimental evaluation shows that our solution is effective in terms of protocol and algorithmic efficiency and provides satisfiable performance with high success rate, reasonable message overhead and runtime.